136-[(63x2:6 + 109) (75:25 +21:3)]:10
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
136-[126:6+109)•(3+7)]:10=
136-[(0.21+109)•10]:10=
136-(109.21•10):10=
136-1092.1:10=
136-109.21=26.79
Răspuns de
0
136-[126:6+109)•(3+7)]:10=
136-[(0,21+109)•10]:10=
136-(109.21•10):10=
136-1092.1:10=
136-109.21=26.79
Sper ca ți-am fost de ajutor!
Succes!
136-[(0,21+109)•10]:10=
136-(109.21•10):10=
136-1092.1:10=
136-109.21=26.79
Sper ca ți-am fost de ajutor!
Succes!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă